2021
DOI: 10.1080/21655979.2021.1982313
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal lncRNA Nuclear Paraspeckle Assembly Transcript 1 (NEAT1)contributes to the progression of allergic rhinitis via modulating microRNA-511/Nuclear Receptor Subfamily 4 Group A Member 2 (NR4A2) axis

Abstract: Allergic rhinitis (AR) is a common chronic disease characterized by inflammation of the nasal mucosa. Long non-coding RNA (LncRNA) has been reported to be involved in the pathogenesis of various diseases. However, the biological roles of lncRNA Nuclear Paraspeckle Assembly Transcript 1 (NEAT1) in AR are still unclear. The mRNA levels of NEAT1, miR-511, and Nuclear Receptor Subfamily 4 Group A Member 2 (NR4A2) were detected by RT-qPCR. The protein levels of exosomal markers were examined by western blot. ELISA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Up-regulated miR-511 NR4A2 and IL13 NEAT1 induced inflammatory cytokine production and apoptosis contributing to the pathogenesis of AR via the miR-511/NR4A2 axis [48].…”
Section: Neat1mentioning
confidence: 99%
“…Up-regulated miR-511 NR4A2 and IL13 NEAT1 induced inflammatory cytokine production and apoptosis contributing to the pathogenesis of AR via the miR-511/NR4A2 axis [48].…”
Section: Neat1mentioning
confidence: 99%
“…The lncRNA/miRNA/mRNA axis is fully evidenced as the major regulatory mechanism of lncRNAs in multiple diseases, including AR (Wang et al 2021 ). Previous study has demonstrated that CDKN2B-AS1 can act as a ceRNA for miRNAs to mediate cellular processes (Guo et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…(4) The lnc‐NEAT1 expression might be related to exacerbated allergic response via inducing the secretion of pro‐inflammatory cytokines and stimulating inflammatory responses; thus, the lnc‐NEAT1 expression was positively related to the disease severity of pediatric AR patients. 14 , 39 …”
Section: Discussionmentioning
confidence: 99%